Effect of Plant Growth on the Transformation of Inorganic Phosphorus in Soils - Sacheti, A K; Saxena, S N (Annals of Arid Zone, 2016)
Five soils from Rajasthan representing various broad soil groups were examined for different phosphate fractions. It was found that soils were rich in calcium phosphate content. Soils after superphosphate addition showed decrease in aluminum bound phosphorus and increase in iron bound phosphorus after crop growth. Correlation studies indicated that plants mainly derive their phosphorus from aluminum hound phosphorus.